Nonaqueous Electrolyte Rechargeable Manganese Batteries with Potassium Manganese Hexacyanoferrate Cathodes - Pyun, Jangwook; Lee, Hyeonjun; Baek, Seunghyeop; Lee, Sangki; Kwon, Hyeju; Lee, Hyeongseok; Yoo, Chung Yul; Chae, Munseok S. (Advanced Science, 2025)
Manganese batteries garnered significant attention as sustainable and cost-effective alternatives to lithium-ion batteries. For the first time, manganese batteries are demonstrated using a manganese hexacyanoferrate cathode and organic electrolyte solution, specifically saturated Mn(ClO₄)₂ in acetonitrile. The manganese hexacyanoferrate cathode exhibits an average operating voltage of 1.7 V and a discharge capacity of 73.4 mAh g−1 at 0.1 A g−1, retaining 71.1% capacity after 1500 cycles at 0.2 A g−1. Diffusion pathways and barriers reveal efficient 3D Mn2⁺ ion diffusion pathways within the manganese hexacyanoferrate framework, with a low migration barrier of 0.514 eV. Despite the promising performance, surface analysis of the Mn metal anode reveals the formation of complex organic/inorganic SEI (solid electrolyte interphase) layers, including MnOx, MnClx, and organic compounds, due to electrolyte decomposition. These findings highlight the critical importance of SEI layer control and electrolyte optimization for enhancing the durability and efficiency of organic electrolyte-based manganese batteries. Manganese batteries are established as a viable next-generation energy storage solution and provide a foundation for further advancements in organic electrolyte-based battery systems.
Keywords: Diffusion pathways; Hexacyanoferrates; Interphase layers; Manganese battery; Manganese hexacyanoferrate; Non-aqueous; Non-aqueous electrolytes; Nonaqueous battery; Organic electrolyte; Solid electrolyte interphase; manganese batteries; manganese hexacyanoferrate; nonaqueous battery; organic electrolyte